The impact of price, service quality, product, and promotion on purchasedecisions at Do'a Ibu Clothing Store in Rantauprapat - Siregar, Asdiah; Siregar, Zulkifli M. Efendi; Hanum, Fauziah (MID Publisher International, 2024)
The purpose of the study is to determine the influence of price, service quality, products and promotions both partially and simultaneously on purchase decisions. This study selected a sample of 100 respondents using the slovin formula. The design of quantitative descriptive research uses multiple linear regression analysis, classical assumption test and hypothesis testing. The results show that all variable indicators meet the requirements of the classical assumption test and have good validity. The results of hypothesis testing found that price variables do not affect purchase decisions, while service quality, product and promotion variables affect purchase decisions partially and simultaneously price variables, service quality, products and promotions affect purchase decisions.